Senyawa Penciri Ekstrak Daun Jati Belanda (Guazuma ulmifolia Lamk) sebagai Anti-Kolesterol - Irmanida Batubara; . Husnawati; Latifah Kosim Darusman; Tohru Mitsunaga (Jurnal Ilmu Pertanian Indonesia, 2017)
Jati belanda (Guazuma ulmifolia Lamk) leaves is traditionally used as slimming and cholesterol reducing agent. This research aims to determine the active component on jati belanda leaves as marker compound for cholesterol reducing agent. The quality of leaves was checked prior to use for next step of analysis. Jati belanda leaves with good quality was extracted by ethanol 30% and the extract was separated by chromatography technique such as open column chromatography and preparative high performance liquid chromatography. The results showed that the quality of samples is meet to the requirement of Indonesian Food and Drug Agency (Badan Pengawas Obat dan Makanan (BPOM)) based on moisture content, ash content, and heavy metal content. Based on the separation results showed that the cholesterol reducing compound from jati belanda is quercetin